A surveillance of estrogen receptor (er), progesterone receptor (pr) and human epidermal growth factor receptor-2 (her-2) status in malignant female breast lesions in Bayelsa state, Nigeria. (2019)
A three (3) year retrospective study of Estrogen Receptor (ER), Progesterone receptor (PR) and Human Epidermal growth factor receptor-2 (HER2) status of previously diagnosed female breast cancers was done using immunohistochemistochemistry. Formalin fixed paraffin embedded (FFPE) tissue blocks of breast cancer cases from 2009-2011 were retrieved from the tissue block archives of the two major tertiary health institutions in the state; Federal Medical Centre, Yenagoa and Niger Delta University Teaching Hospital, Okolobiri. The result of this research work revealed the incidences of the receptor status as it occurred among 36 malignant female breast lesions in Bayelsa State as follows; ER+ve=13.8%, ER-ve=86.2%, PR+ve=19.4%, PR-ve=80.6%, HER2+ve=33.3% HER2-ve=66.7%, TR+=13.3% while TR-=55.7%. The statistical analysis of the result revealed that no significant relationship exists between the various age groups and the respective incidences of the receptor status. In the same vein, no significant relationship exists between the respective histopathologic diagnosis of the samples used and the incidences of the respective receptor status except for ER+ve and ER-ve whose incidences were found to have a significant relationship with the histopathologic diagnosis. This by implication means that the incidences of ER+ve and ER-ve respectively maybe dependent on the histopathologic diagnosis at P < 0.05. In conclusion, it is worthy of note here that while researches are on to tackle cancers and breast cancer in particular, there is need for even distribution of IHC facility or other molecular studies in the nation because of its role in breast cancer prevention strategies and patient management.